Is eye-color selection a legitimate business? - Osland, Asbjorn, (SAGE Knowledge. Cases., 2019)
The Fertility Institutes, established by Dr. Jeffrey Steinberg, offers preimplantation genetic diagnosis (PGD) to help prospective parents choose the gender of their child through trait selection. In 2009, Steinberg had planned to offer hair and eye-color selection, but postponed the service due to media concern over so-called "designer babies." Steinberg continued refining the technology for eye-color selection and began offering it again in March 2018. This time there was no media-related controversy. This case explores the factors around legitimizing new medical innovations and advancing the business related to them. The case reveals how improvements in technology have enabled once radical procedures to gain ethical and regulatory acceptance in the United States.